PENGARUH SELF REGULATED LEARNING, SELF EFFICACY DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PESERTA DIDIK SMANISDA - Gebrylia Miliani Tri Subekti; Riza Yonisa Kurniawan (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
This study aims to see whether self-regulated learning, Self-efficacy and learning motivation have an effect on economic learning outcomes for class X students of SMA Negeri 1 Sidoarjo in the 2021-2022 academic year on economics subjects. The research method used is descriptive quantitative, with interviews, tests and questionnaires to obtain data. Data were analyzed using SPSS 24 software to test the validity and reliability and WarpPLS 7.0 for research results. The results showed that (1) Self-Regulated Learning had a negative effect on the Self Efficacy of students in class X SMA Negeri 1 Sidoarjo, (2) Self-Regulated Learning had a negative effect on learning outcomes for students in class X SMA Negeri 1 Sidoarjo, (3) Motivation for learning had an effect on positive effect on Self Efficacy of students in class X SMA Negeri 1 Sidoarjo, (4) Self Efficacy has a negative effect on learning outcomes of students in class X SMA Negeri 1 Sidoarjo, (5) learning motivation has a positive effect on learning outcomes of students in class X SMA Negeri 1 Sidoarjo